Ethics in Criminal Justice: John Dewey Revisited - Smith, Michael Clay (American journal of criminal justice, 1986)
John Dewey has much to say to contemporary criminal justice educational strategies, particularly in respect to broadening the curriculum to include exposure to the humanities, values exploration, and moral decision-making. The case study method, coupled with Socratic teaching use of varied materials from the humanities, can approach an optimal learning experience within the Dewayan model. This educational model is offered in response to the calls for sensitive, holistic criminal justice practitioners in the modern age.